Design ideation stage: an investigation into the act of sketching and mental imagery in novice designers - Tedjosaputro, Mia Ardiati (2018)
This PhD project embarks on a journey to investigate how novice designers behave during the idea generation stage. It is the first stage when a designer becomes aware of design briefs or requirements. Key results are presented briefly. In general the study confirms that sketching provides better assistance in comparison to mental imagery. These results are unsurprising, however in three out of six phenomena were supported in mental imagery sessions as effectively as in sketching sessions. This study also suggests differences between interplays of mind-body environment in described sketching and mental imagery sessions. Common patterns and operational design actions in specific design intentions and sub-intentions are presented. In addition, this study suggests similarities between architecture and product design in terms of idea generation processes. The results challenge previous studies by making contributions to the observed research gap: the role of internal and external representations in novice designers with fewer previously-generated and ready-to-be-deployed solutions; and relative advantages between design environments (with and without externalisations). This study adds knowledge in the design cognition and process field through the view of designing as embodied experience.